MRI CHANGES AMONG PATIENTS OF ECLAMPSIA AND PREECLAMPSIA WITH ASSOCIATED NEUROLOGICAL SYMPTOM ANALYSIS - Umar, Tayyaba; Gilani, Atifa; Tasnim, Amber; Yousaf, Muhammad Ali; Umar, Sara; Mehboob, Annas; Gilani, Amna; Gilani, Fatima (Journal of Ayub Medical College Abbottabad, 2022)
Background: Pregnancy poses some stress on normal homeostasis of the human body and brings changes in the body which predisposes the individual towards various pathological conditions as well. Objective: Objective of the study was to determine the magnetic resonance imaging (MRI) changes and clinical symptoms associated with these changes among patients of eclampsia and preeclampsia managed at tertiary care unit. It was a cross-sectional study, conducted at Gynaecology and obstetrics department Pak Emirates Military Hospital (PEMH) Rawalpindi. January to June 2019. Methods: A total of 80 pregnant women who were diagnosed by consultant obstetrician for eclampsia or pre-eclampsia were included in the study. All the patients underwent Plain MRI brain including TIWI, T2WI, FLAIR, DWI, ADC, GRE and SWI sequences at radiology department of PEMH RWP. Positive MRI findings were defined as presence of cerebral oedema, infarction, cerebral venous sinus thrombosis and cerebral haemorrhage. Headache, seizures, altered mental status and visual problems were correlated with MRI changes among the target population. Results: Out of 80 pregnant women with eclampsia or pre-eclampsia, 49 (61.2%) had no changes on MRI while 31 (38.8%) had significant changes on MRI. Cerebral oedema 12 (15%) was the most common MRI finding followed by cerebral haemorrhage 8 (10%). Mean age of participants was 36.33±2.238 years. With Pearson chi-square analysis, it was found that presence of seizures and altered mental state had statistically significant relationship with presence of MRI findings among the target population. Conclusion: MRI changes were a common finding among the patients of eclampsia or pre-eclampsia. Cerebral oedema was the commonest finding in our study. Patients with serious clinical symptoms like seizures and altered mental state had more chances of having MRI changes as compared to patients without the serious clinical symptoms.